2023
DOI: 10.3390/nu15040943
|View full text |Cite
|
Sign up to set email alerts
|

ATP and NAD+ Deficiency in Parkinson’s Disease

Abstract: The goal of this study is to identify a signature of bioenergetic and functional markers in the muscles of individuals with Parkinson’s disease (PD). Quantitative physiological properties of in vivo hand muscle (FDI, first dorsal interosseus) and leg muscle (TA, Tibialis Anterior) of older individuals with PD were compared to historical age/gender-matched controls (N = 30). Magnetic resonance spectroscopy and imaging (MRS) were used to assess in vivo mitochondrial and cell energetic dysfunction, including maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…We found lower levels of NADH, nicotinamide, nicotinic acid (quinolinate metabolites, and the precursors and metabolites of NAD+ and NADP+) in P than in C. This reduction in NAD levels may have a role in the neurotoxicity in PD. These findings are aligned with previous research; for example, one study found that NAD levels were significantly lower in the muscles of 30 PD patients compared to age-matched controls ( Mischley et al, 2023 ), while a clinical trial phase I study tested the effect of oral administration of nicotinamide riboside (NR) in 30 PD patients, and found that NR increases the levels of NAD, stimulates the transcriptional upregulation of the processes related to mitochondrial, lysosomal, and proteasomal activities in skeletal muscles and blood cells, and decrease the inflammatory cytokines ( Brakedal et al, 2022 ). Another study found that NR increased NAD, which led to not only ameliorating the mitochondrial functions in induced pluripotent stem cells isolated from PD patients but also preventing age-related dopaminergic neuronal loss and motor deficits in fly models of GBA-PD ( Schöndorf et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…We found lower levels of NADH, nicotinamide, nicotinic acid (quinolinate metabolites, and the precursors and metabolites of NAD+ and NADP+) in P than in C. This reduction in NAD levels may have a role in the neurotoxicity in PD. These findings are aligned with previous research; for example, one study found that NAD levels were significantly lower in the muscles of 30 PD patients compared to age-matched controls ( Mischley et al, 2023 ), while a clinical trial phase I study tested the effect of oral administration of nicotinamide riboside (NR) in 30 PD patients, and found that NR increases the levels of NAD, stimulates the transcriptional upregulation of the processes related to mitochondrial, lysosomal, and proteasomal activities in skeletal muscles and blood cells, and decrease the inflammatory cytokines ( Brakedal et al, 2022 ). Another study found that NR increased NAD, which led to not only ameliorating the mitochondrial functions in induced pluripotent stem cells isolated from PD patients but also preventing age-related dopaminergic neuronal loss and motor deficits in fly models of GBA-PD ( Schöndorf et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Numerous pathogenic processes, including IR, oxidative stress, immunology, and inflammation, may overlap between MetS and PD [ 8 , 33 , 34 ]. This overlap suggests that PD should be treated as a metabolic disease [ 35 , 36 ]. IR is a key factor in type 2 diabetes and is now recognized as an important mechanism in the association between DM and PD.…”
Section: Discussionmentioning
confidence: 99%
“…As critical components in cellular metabolism, COA-SH and ATP are strongly linked to cell growth, death, and energy provision. 19,20 Abnormal levels of these molecules in the body closely correlate with various diseases, 21 such as cardiovascular diseases, 22 Parkinson's disease, 23 and Alzheimer's disease. 24 Therefore, the development of point-of-care testing (POCT) sensors capable of directly and accurately detecting COA-SH and ATP holds significant importance.…”
Section: Introductionmentioning
confidence: 99%